1991
DOI: 10.1002/aic.690370314
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the three‐dimensional turbulent flow in stirred tanks

Abstract: Efforts to model the turbulent flow in stirred tanks Kolar's (1982)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(96 citation statements)
references
References 31 publications
5
90
0
1
Order By: Relevance
“…In the case of bioprocessing, shear stresses are present during the separation, purification, shipping, and handling of protein based products. 13 For example, processing steps involving ultrafiltration reactors, 120,121 stirred tanks, 122,123 homogenizers, 124 and pumps 53,125 induce high shear stresses. Simulated lobe pump studies have shown that high shear stress in these processing steps is sufficient to cause minor changes to protein structure.…”
Section: Implications In Physiology and Bioprocessingmentioning
confidence: 99%
“…In the case of bioprocessing, shear stresses are present during the separation, purification, shipping, and handling of protein based products. 13 For example, processing steps involving ultrafiltration reactors, 120,121 stirred tanks, 122,123 homogenizers, 124 and pumps 53,125 induce high shear stresses. Simulated lobe pump studies have shown that high shear stress in these processing steps is sufficient to cause minor changes to protein structure.…”
Section: Implications In Physiology and Bioprocessingmentioning
confidence: 99%
“…In the case of a Rushton turbine the jet flow slowly changes direction from a circumferential direction to a more radial direction with increasing radial distance from the axis 4,17,18 . Thin shear layer theory can be applied and an approximate self-similar solution can be obtained for the jet (see Yoon et al 15 ).…”
Section: Decomposition Of Mean Flowmentioning
confidence: 99%
“…The earliest attempts at numerical simulations of flow field in mechanically agitated vessels employed an approach called impeller boundary condition approach (Harvey and Greaves, 1982;Middleton et al, 1986;Pericleous and Patel, 1987;Ranade et al, 1989;Ranade and Joshi, 1990;Kresta and Woods, 1991;Fokema et al, 1994;Armenante et al, 1994). In this approach, impeller was not physically modeled and was represented either in terms of boundary conditions at the surface of the volume swept by it or in terms of source terms distributed throughout its volume.…”
Section: Cfd Modeling Of Mechanically Agitated Baffled Tanksmentioning
confidence: 99%